fSCIG 10% in pediatric primary immunodeficiency diseases: a European post-authorization safety study - Peter Čižnár; Marion Roderick; Helen Schneiderova; Miloš Jeseňák; Gergely Kriván; Nicholas Brodszki; Stephen Jolles; Charles Atisso; Katharina Fielhauer; Shumyla Saeed-Khawaja; Barbara McCoy; Leman Yel (Allergy, Asthma & Clinical Immunology, 2024)
Abstract Background The safety, tolerability, and immunogenicity of hyaluronidase-facilitated subcutaneous immunoglobulin (fSCIG) 10% (dual-vial unit of human immunoglobulin 10% and recombinant human hyaluronidase [rHuPH20]) were assessed in children with primary immunodeficiency diseases (PIDs). Methods This phase 4, post-authorization, prospective, interventional, multicenter study (NCT03116347) conducted in the European Economic Area, enrolled patients aged 2 to < 18 years with a documented PID diagnosis who had received immunoglobulin therapy for ≥ 3 months before enrollment. New fSCIG 10% starters underwent fSCIG 10% dose ramp-up for ≤ 6 weeks (epoch 1) before receiving fSCIG 10% for ≤ 3 years (epoch 2); patients pretreated with fSCIG 10% entered epoch 2 directly. The primary outcome was the number and rate (per infusion) of all noninfectious treatment-related serious and severe adverse events (AEs). Results In total, 42 patients were enrolled and dosed (median [range] age: 11.5 [3–17] years; 81% male; 23 new starters; 19 pretreated). Overall, 49 related noninfectious, treatment-emergent AEs (TEAEs) were reported in 15 patients; most were mild in severity (87.8%). No treatment-related serious TEAEs were reported. Two TEAEs (infusion site pain and emotional distress) were reported as severe and treatment-related in a single new fSCIG 10% starter. The rate of local TEAEs was lower in pretreated patients (0.1 event/patient-year) versus new starters (1.3 events/patient-year). No patients tested positive for binding anti-rHuPH20 antibodies (titer of ≥ 1:160). Conclusions No safety signals were identified, and the incidence of local AEs declined over the duration of fSCIG 10% treatment. This study supports fSCIG 10% long-term safety in children with PIDs. Trial registration number (ClinicalTrials.gov) NCT03116347.